SENJAKALA PUSAT SUMBER BELAJAR DI PERGURUAN TINGGI - Imam Fitri Rahmadi (Prodi PPKn FKIP Universitas Pamulang, 2017)
Learning resources center (LRC) was being a place for developing learning systems, training regarding learning skills and instructions, and providing learning resources in university. However, at this time, the LRC existence in university tended to decrease compared to the condition at its establishment. This article discusses the decrease of the LRC existence, particularly regarding the opportunity of the LRC implementation that is reviewed from the formal basis, policies, and funding sources based on the results of the evaluation research by CIPP evaluation model. The research was conducted in the State University of Jakarta’s learning resources center by a questionnaire which is implements stratified random sampling toward 212 students and 100 lecturers, non-participatory observation, interview with the stakeholders, and documents study of the LRC since 1986 to 2015. The data were analyzed by statistical descriptive and qualitative. The research found that the opportunity for LRC implementation is very weak, due to no a substantively supportive policy and insufficient funding source, even though at the time of its establishment has a strong formal basis. A very weak opportunity could lead to the stunned of LRC in university. Hence, stakeholders should formulate policies that substantially support, and strive fixed and adequate funding sources to reinforce the opportunity of LRC implementation in university for the future.